Scenic design and lighting techniques : a basic guide for theatre - Gloman, Chuck B. (Focal Press, 2007)
Basic. This is the key word in Scenic Design and Lighting Tecniques: A Basic Guide for Theatre, written by two seasoned professionals with over twenty years of experience. This book is designed to show you how to turn a bare stage into a basic set design, without using heavy language that would bog you down. From materials and construction to basic props and lighting, this book explains all you will need to know to build your set and light it.